THE FINANCIAL CRISIS IN EUROPE AND IN ROMANIA. FEATURES AND COMBATING MEASURES - Magdalena RĂDULESCU (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice)
The crisis triggered in 2007-2008 in the USA and then globally manifested strongly and affected many areas and categories of people. Through its specific features, it proved that the current regulatory system is no longer viable and it has to be reformed so that in the future to alleviate some of the negative effects felt in the context of the last international financial and economic crisis. The measures adopted were aimed at the fiscal, monetary and the income policy. Only used in combination, these policies proved effective under crisis conditions and determined the economic recovery.